2003
DOI: 10.1161/01.cir.0000103122.10021.f2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time to Treatment on Mortality After Prehospital Fibrinolysis or Primary Angioplasty

Abstract: MD; for the Comparison of Angioplasty and Prehospital Thrombolysis In acute Myocardial infarction (CAPTIM) Investigators*Background-CAPTIM was a randomized trial comparing prehospital thrombolysis with transfer to an interventional facility (and, if needed, percutaneous intervention) with primary percutaneous coronary intervention (PCI) in patients with ST-segment-elevation myocardial infarction (STEMI). Because the benefit of thrombolysis is maximal during the first 2 hours after symptom onset, and because pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0
26

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(128 citation statements)
references
References 35 publications
(35 reference statements)
5
92
0
26
Order By: Relevance
“…There was no difference at 30 days in the primary composite of death, non-fatal reinfarction, and non-fatal stroke (8.2% for fibrinolysis versus 6.2% for PCI, Pϭ0.29) or in mortality alone (3.8% versus 4.8%, Pϭ0.61). Furthermore, as described in a provocative analysis by Steg et al 6 in the current issue of Circulation, there was a strong trend toward lower mortality (2.2% versus 5.7%, Pϭ0.058) and a reduction of cardiogenic shock (1.3% versus 5.3%, Pϭ0.032), but no difference in the primary triple endpoint (7.4% versus 6.6%, Pϭ0.86) in patients treated with prehospital fibrinolysis within 2 hours of symptom onset. Thus, the abovedescribed superiority of PCI over fibrinolysis appears not always to be present in a small but important subgroup of patients, ie, those who can receive treatment in the first 2 hours after symptom onset.…”
Section: See P 2851mentioning
confidence: 97%
“…There was no difference at 30 days in the primary composite of death, non-fatal reinfarction, and non-fatal stroke (8.2% for fibrinolysis versus 6.2% for PCI, Pϭ0.29) or in mortality alone (3.8% versus 4.8%, Pϭ0.61). Furthermore, as described in a provocative analysis by Steg et al 6 in the current issue of Circulation, there was a strong trend toward lower mortality (2.2% versus 5.7%, Pϭ0.058) and a reduction of cardiogenic shock (1.3% versus 5.3%, Pϭ0.032), but no difference in the primary triple endpoint (7.4% versus 6.6%, Pϭ0.86) in patients treated with prehospital fibrinolysis within 2 hours of symptom onset. Thus, the abovedescribed superiority of PCI over fibrinolysis appears not always to be present in a small but important subgroup of patients, ie, those who can receive treatment in the first 2 hours after symptom onset.…”
Section: See P 2851mentioning
confidence: 97%
“…A randomized trial of early, in-ambulance thrombolysis versus primary PCI found no CS among patients assigned to prehospital thrombolysis. 7 Among PCI-assigned patients, just 0.5% developed CS in the group randomized Ͻ2 hours from symptom onset. A major focus of public health campaigns is the very early recognition and reperfusion of MI, which should reduce CS incidence.…”
Section: Identification Of Patients At Riskmentioning
confidence: 99%
“…É importante ressaltar que a segurança da transferência para um hospital terciário habilitado para ICP de urgência já foi verificada por alguns estudos [323][324][325] .…”
Section: -Intervenção Coronária Percutânea De Salvamentounclassified